Analisis Faktor Keberhasilan Kemajuan Ekonomi Nelayan Desa Bendar Kecamatan Juwana Kabupaten Pati - Oktadina Sekarwangi; Pudji Astuti; Sulistyowati . (Journal of Politic and Government Studies, 2016)
This research has a purpose to find out success factors for economic progress of the fisherman in Bendar Village, Juwana District, Pati Regency by observing the current economic progress in the village.The study uses the theory of social change of the fishermen in Bendar Village, Community Development and Social Capital. This study also use a qualitative descriptive research method. Research data were collected by interview and observation by involving informants from the Municipal Office of Maritime Affairs and Fisheries of Pati Regency and Fishermen in Bendar Village.The results of this research obtained from the factors that determine the ecomonic progress of the fishermen in Bendar Village. Some forms of economic progress of fishermen in Bendar Village look by traditional fishermen transtution into a modern fishermen since 1995, the increase in the income of fishermen, the changes in power consumption and some benefits for infrastructure development in Bendar Village and social development of community in Bendar Village.The factors that affecting the economic progress of fishermen in Bendar Village comes from the social capital of community in Bendar Village that divide to social capital in cultural, social and economic. Then the government policy that licensing certificates vessel can be used as additional collateral to the Bank and the  dab blood relations of mutually shared by many fishermen community in Bendar Village.Economic progress in Bendar Village didn’t have an impact on all aspects. In the aspect of education of fishermen community in Bendar Village still considered not important for improve welfare in the future. The most important factor in the economic progress of fishermen is the intervention from government that happens by a suggestion of the one of fishermen in Bendar Village.